Spatial transcriptomics reveals prognosis‐associated cellular heterogeneity in the papillary thyroid carcinoma microenvironment - Kai Yan; Qing‐Zhi Liu; Rong‐Rong Huang; Yi‐Hua Jiang; Zhen‐Hua Bian; Si‐Jin Li; Liang Li; Fei Shen; Koichi Tsuneyama; Qing‐Ling Zhang; Zhe‐Xiong Lian; Haixia Guan; et al. (Clinical and Translational Medicine, 2024)
Abstract Background Papillary thyroid carcinoma (PTC) is the most common malignant endocrine tumour, and its incidence and prevalence are increasing considerably. Cellular heterogeneity in the tumour microenvironment is important for PTC prognosis. Spatial transcriptomics is a powerful technique for cellular heterogeneity study. Methods In conjunction with a clinical pathologist identification method, spatial transcriptomics was employed to characterise the spatial location and RNA profiles of PTC‐associated cells within the tissue sections. The spatial RNA‐clinical signature genes for each cell type were extracted and applied to outlining the distribution regions of specific cells on the entire section. The cellular heterogeneity of each cell type was further revealed by ContourPlot analysis, monocle analysis, trajectory analysis, ligand–receptor analysis and Gene Ontology enrichment analysis. Results The spatial distribution region of tumour cells, typical and atypical follicular cells (FCs and AFCs) and immune cells were accurately and comprehensively identified in all five PTC tissue sections. AFCs were identified as a transitional state between FCs and tumour cells, exhibiting a higher resemblance to the latter. Three tumour foci were shared among all patients out of the 13 observed. Notably, tumour foci No. 2 displayed elevated expression levels of genes associated with lower relapse‐free survival in PTC patients. We discovered key ligand–receptor interactions, including LAMB3–ITGA2, FN1–ITGA3 and FN1–SDC4, involved in the transition of PTC cells from FCs to AFCs and eventually to tumour cells. High expression of these patterns correlated with reduced relapse‐free survival. In the tumour immune microenvironment, reduced interaction between myeloid‐derived TGFB1 and TGFBR1 in tumour focus No. 2 contributed to tumourigenesis and increased heterogeneity. The spatial RNA‐clinical analysis method developed here revealed prognosis‐associated cellular heterogeneity in the PTC microenvironment. Conclusions The occurrence of tumour foci No. 2 and three enhanced ligand–receptor interactions in the AFC area/tumour foci reduced the relapse‐free survival of PTC patients, potentially leading to improved prognostic strategies and targeted therapies for PTC patients.